A serological and molecular study on Francisella tularensis in rodents from Hamadan province, Western Iran. (February 2020) - Hemati, Majid; Khalili, Mohammad; Rohani, Mahdi; Sadeghi, Balal; Esmaeili, Saber; Ghasemi, Ahmad; Mahmoudi, Ahmad; Gyuranecz, Miklós; Mostafavi, Ehsan
Highlights: The present study aimed to investigate the infection of rodents, as potential reservoirs of tularemia in Iran. The most frequent trapped species belonged to Meriones persicus (75.5%). The tube agglutination test was performed on rodent serum, and three out of 407 serum samples were positive (0.74%) for Francisella tularensis . Five out of 433 (1.15%) extracted DNA samples were PCR positive (1.15%). Considering that all the seropositive rodents belonged to jirds, which are widespread in the Iranian Plateau, the risk of human infections acquired from these animals is high in the studied region. Abstract: Introduction and purpose: Tularemia is a zoonotic disease, the most important hosts of which are rodents. Endemic regions and reservoirs of F. tularensis are not well-researched areas in Iran. The present study aimed to study F. tularensis infection in the rodent populations of western Iran. Materials and methods: Samples were collected in different areas of Kabudar Ahang County in Hamadan province (west of Iran) from 2014 to 2017. Tularemia serological and molecular tests were conducted using the tube agglutination test and Real-time PCR method tracking the ISFtu2 gene. Positive serum samples were evaluated for cross-reactivity with brucellosis. Results: A total of 433 rodents, collected from 33 localities, were included in the study. The most abundant species belonged to the Persian jird ( Meriones persicus ; 75.5%), and Libyan jird ( Meriones libycus ; 10.1%). Among the studied samples, three (0.74 %) were seropositive and five (1.15%) were PCR positive. Seropositive samples were two M. persicus and one M. libycus, and PCR positive rodents were four M. persicus and one M. vinogradovi . Tularemia seropositive samples showed no cross-reactivity with brucellosis. Conclusion: Given the presence of infection in rodents with tularemia agent in the studied area, it is crucial to elucidate the risks of rodent exposure to tularemia for physicians, health personnel and the general population.